Cosmopolitan Communication Studies : Toward Deep Internationalization - Carola Richter; Melanie Radue; Christine Horz-Ishak; Anna Litvinenko; Hanan Badr; Anke Fiedler (transcript, 2025)
This volume proposes a “deep internationalization” of media and communication studies by offering insights and guidance on how to integrate a cosmopolitan perspective in a variety of subfields of this discipline. Building on debates on de-Westernization and cosmopolitanism, the contributors advocate for the inclusion of both global and local perspectives and context-led approaches. They argue that acknowledging and incorporating epistemologies, topics, and methodologies from diverse regions, contexts, and backgrounds will enhance the comprehensiveness and relevance of their discipline and foster a more inclusive and meaningful understanding in communication studies.